PVTx measurements and other derived volumetric properties of the binary ((1-propanol + n-pentane)) mixtures in the critical and supercritical regions. (June 2017) - Abdulagatov, Ilmutdin M.; Bazaev, Akhmed R.; Bazaev, Emil A.; Dzhapparov, Tamerlan A.
Graphical abstract: Highlights: PVT measurements of 1-propanol +  n -pentane in the critical and supercritical regions. Excess and partial molar volumes. Krichevskii parameter and thermodynamic properties of dilute mixture near the critical point. Isomorphic thermodynamic behaviour of the mixture near the critical curve. Abstract: The PVTx properties of binary (1-propanol +  n -pentane) mixture have been measured over wide temperature and pressure ranges from (306.15 to 573.15) K for densities between (15.52 and 663.69) kg·m −3 up to 49.09 MPa for four concentrations (0.2, 0.5, 0.8, and 0.9 mol fraction of n -pentane). The well-known high-temperature and high-pressure constant-volume piezometer technique was used for measurements of the PVTx relationship. The measurements were concentrated in the critical and supercritical regions in order to study the features of the mixture critical curve behaviour (critical phenomena in the (1-propanol +  n -pentane) mixture and other derived thermodynamic properties near the liquid-gas critical points. The combined expanded uncertainty of the density ( ρ ), pressure ( P ), temperature ( T ), and concentration ( x ), measurements at the 95% confidence level with a coverage factor of k  = 2 is estimated to be 0.2% (density in the liquid phase), 0.3% (density in the gas phase); 0.5% (density in the critical and supercritical regions); 0.05% (pressure), 15 mK, and 0.01 mol%. The critical curve values ( T C - x ), ( P C - x ), and ( ρ C - x ), were determined from the measured PVTx results. The value of the Krichevskii parameter ( ∂ P / ∂ x ) T C V C ∞  = 7.985 MPa for (1-propanol +  n -pentane) mixture was estimated from the present and reported critical curve and the directly measured P - x results along the critical isochore-isotherm of pure 1-propanol. The critical curve values were also used to study the critical phenomena (isomorphism in the binary mixture) in the (1-propanol +  n -pentane) mixture. In particular, the characteristic reduced temperature and density differences, which determine the isomorphic thermodynamic behaviour (pure-like and mixture-like critical behaviour) of the mixture, were estimated using the critical curve values. The measured PVTx values were also used to calculate the derived volumetric properties such as excess and partial molar volumes of n -pentane near the critical point of pure 1-propanol.